Mongolia : Financial System Stability Assessment. (IMF Staff Country Reports; Country Report ;, 2011)
The Mongolian financial system is dominated by commercial banks. The nonbank financial sector, including insurance and the stock market, is small. The current level of dollarization exposes Mongolia's financial system to risk. The authorities are in the process of establishing the Development Bank of Mongolia as a state-owned limited liability company. They should carefully consider the options for financing the Development Bank and their budget and other implications. Aggregate financial soundness indicators for the banking system show a partial recovery from the crisis.